2015
DOI: 10.1038/ncomms9079
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid glasses from strong and fragile metal-organic framework liquids

Abstract: Hybrid glasses connect the emerging field of metal-organic frameworks (MOFs) with the glass formation, amorphization and melting processes of these chemically versatile systems. Though inorganic zeolites collapse around the glass transition and melt at higher temperatures, the relationship between amorphization and melting has so far not been investigated. Here we show how heating MOFs of zeolitic topology first results in a low density ‘perfect' glass, similar to those formed in ice, silicon and disaccharides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

30
416
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(469 citation statements)
references
References 47 publications
30
416
2
8
Order By: Relevance
“…13 Because the amorphous MOFs are initiated by crystal collapse, rather than by melt quenching from temperatures above melting points T m , they were not viewed as typical glasses. 11,13 Strikingly, the amorphous MOFs are of high thermal stability and, thus, can be used as a model system to make a complete demonstration of the glass transition for the amorphous materials between the amorphous phases and supercooled liquids. It is also expected that the studies of the amorphization in MOFs can offer new insight into the transition itself.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Because the amorphous MOFs are initiated by crystal collapse, rather than by melt quenching from temperatures above melting points T m , they were not viewed as typical glasses. 11,13 Strikingly, the amorphous MOFs are of high thermal stability and, thus, can be used as a model system to make a complete demonstration of the glass transition for the amorphous materials between the amorphous phases and supercooled liquids. It is also expected that the studies of the amorphization in MOFs can offer new insight into the transition itself.…”
mentioning
confidence: 99%
“…Thus, a question as to whether the amorphous materials initiated by damaged crystals have the basic features of the glass transition involved in melt-quenched glasses needs to be clarified. Recent studies of metal-organic frameworks (MOFs), which have unique structures of porous three-dimensional network constructed by centered metals and organic linkers, 11,12 found that amorphization can occur upon heating crystals to collapse. 13 Because the amorphous MOFs are initiated by crystal collapse, rather than by melt quenching from temperatures above melting points T m , they were not viewed as typical glasses.…”
mentioning
confidence: 99%
“…For comparison, we have also investigated the thermal effects on the vibrational spectra of ZIF-8 (whose linker is mIm = 2-methylimidazolate), which does not amorphize thermally. 21 It is worth noting that these materials can also amorphize through other sources of external stimuli, such as pressure 22 and mechanical impact. 23 However, it has been suggested that the mechanisms for the various routes to amorphization are different, with a shear instability being the likely cause of the mechanically induced amorphization.…”
mentioning
confidence: 99%
“…To strengthen this claim, we investigated the value of for ZIF-8, which is well accepted not to amorphize thermally. 21 Importantly, the linker is different, 2-methylimidazole (mIm), so we could provide another value of , this time applied to Zn(mIm)4 tetrahedral deformations. The resultant value for ZIF-8 is 0.032 cm -1 K -1 , with an adjusted R 2 value of 0.995 for the curve fitting, hence prompting the claim that a lower value of implies an increased thermal stability to amorphization.…”
mentioning
confidence: 99%
“…irreversible trapping of species such as radioactive iodine (Chapman et al, 2011). However, we still have a lot to learn about the disordered phases of MOFs and the mechanisms of crystal-to-disordered transitions, as illustrated by the recent discovery of glassforming liquid MOFs (Bennett et al, 2015) and the evidence that correlated disorder can play a strong role even in crystalline MOF structures (Cliffe et al, 2014).…”
mentioning
confidence: 99%